God, slavery and early Christianity: divine possession and ethics in the Shepherd of Hermas - Bonar, Chance E. (Cambridge University Press, 2025)
""Ancient Christians understood themselves to be enslaved to God, which affected their ethics, theology, and self-understanding. This book analyzes the Shepherd of Hermas, an overlooked early Christian text written by an enslaved person, which was nearly included in the New Testament, to map the effects of divine slavery.""--